Silica Nanoparticle‐induced Cytokine Responses in BEAS‐2B and HBEC3‐KT Cells: Significance of Particle Size and Signalling Pathways in Different Lung Cell Cultures; Basic and Clinical Pharmacology and Toxicology; Vol. 122, iss. 6 - Lag M. Marit; Skuland T. S. Tonje; Godymchuk (Godimchuk) A. Yu. Anna Yuryevna; Nguyen Thu H.T.; Pham Hang L.T; Refsnes M. Magne (2018, 2018)
Title screen